LINGUAL ANALYSIS OF IDIOMS COMPARISON IN UZBEK AND ENGLISH LANGUAGES - Xushmanova Shaxnoza Ibragimovna; Xudoyqulova Zilola Ilhomovna; Djurayeva Gulbahor Eshmuratovna (Journal of new century innovations, 2023)
Abstract: рhraseology is an integral and richest part of any language. In idioms we see historical signs of language formation, find unique features of culture and education, which significantly influenced the development of language. Idioms have an original character, it is very difficult to find analogues in the language of translation. For example, along with purely national idioms in English and Uzbek phraseology, there are many international idioms that help to find appropriate meaning in translation. The phraseological fund of any language is a complex conglomerate of native and borrowed idioms with a clear dominance of the first ones. Some idioms retain stylistic elements - representatives of previous eras, reflecting the priorities of the time. The phraseological structure of Uzbek and English languages is very various, but have similar meaning. The considerable part of it is made by units with national and thematic semantics. In article in comparative aspect semantic properties of idioms of the Uzbek and English languages are considered.